Can Abstract State Machines Be Useful in Language Theory? - Gurevich, Yuri; Veanes, Margus; Wallace, Charles (Theoretical Computer Science, 2007)
The abstract state machine (ASM) is a modern computation model. ASMs and ASM based tools are used in academia and industry, albeit on a modest scale. They allow you to give high-level operational semantics to computer artifacts and to write executable specifications of software and hardware at the desired abstraction level. In connection with the 2006 conference on Developments in Language Theory, we point out several ways that we believe abstract state machines can be useful to the DLT community.